Recovery of strength after exercise-induced muscle damage in vegetarians consuming the upper and lower ends of protein recommendations for athletes - Presti, N.; Rideout, T. C.; Temple, J. L.; Bratta, B.; Hostler, D. (Nutrients, 2025)
Background/Objective: Plant-based protein is less bioavailable than animal protein. It is unclear if the protein recommendations for athletes should be increased when following a vegetarian diet. This study`s purpose is to document the recovery of strength and power, as well as to assess soreness after exercise-induced muscle damage (EIMD), in people following a vegetarian diet while consuming the lower (1.2 g/kg/day) and upper (2.0 g/kg/day) ends of protein recommendations for athletes.